Strategic Financial Management for Enhanced Educational Infrastructure: A Case Study of State Elementary School 04 Samsam, Kandis Riau Indonesia - Amaluddin, Muhammad Rizqi; Ismail, Nurmahmudi; Munastiwi, Erni (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2023)
This study explores the effectiveness of financial management at State Elementary School 04 Samsam, Kandis, in enhancing educational infrastructure. The research uses a qualitative approach and strategically allocates government and external funds for school facilities. The methodology involved a detailed analysis using the Miles and Huberman model, emphasizing data collection, reduction, and interpretation. Findings reveal the school's financial success hinges on meticulous planning, prioritization, and robust stakeholder engagement. Key strategies include a multi-tiered approach to budgeting, emphasizing immediate and long-term infrastructure needs, and leveraging local company contributions alongside government funding. The study underlines the significance of strategic financial governance and stakeholder participation in educational settings. While insightful, the research's scope is limited to one institution, suggesting a need for broader investigation. Overall, this case study contributes to the broader discourse on effective financial practices in schools, highlighting their impact on educational quality and infrastructure development.